A Distinct Switch in Interactions of the Histone H4 Tail Domain upon Salt-dependent Folding of Nucleosome Arrays - Pepenella, Sharon (American Society for Biochemistry and Molecular Biology, 2014)
The core histone tail domains mediate inter-nucleosomal interactions that direct folding and condensation of nucleosome arrays into higher-order chromatin structures. The histone H4 tail domain facilitates inter-array interactions by contacting both the H2A/H2B acidic patch and DNA of neighboring nucleosomes (1, 2). Likewise, H4 tail-H2A contacts stabilize array folding (3). However, whether the H4 tail domains stabilize array folding via inter-nucleosomal interactions with the DNA of neighboring nucleosomes remains unclear. We utilized defined oligonucleosome arrays containing a single specialized nucleosome with a photo-inducible cross-linker in the N terminus of the H4 tail to characterize these interactions. We observed that the H4 tail participates exclusively in intra-array interactions with DNA in unfolded arrays. These interactions are diminished during array folding, yet no inter-nucleosome, intra-array H4 tail-DNA contacts are observed in condensed chromatin. However, we document contacts between the N terminus of the H4 tail and H2A. Installation of acetylation mimics known to disrupt H4-H2A surface interactions did not increase observance of H4-DNA inter-nucleosomal interactions. These results suggest the multiple functions of the H4 tail require targeted distinct interactions within condensed chromatin.